Antidepressant continuation in pregnancy and risk of gestational diabetes. Issue 9 (12th July 2019) - Wartko, Paige D.; Weiss, Noel S.; Enquobahrie, Daniel A.; Chan, K.C. Gary; Stephenson‐Famy, Alyssa; Mueller, Beth A.; Dublin, Sascha
Abstract: Purpose: Previous studies observed modestly higher risk of gestational diabetes (GDM) associated with antidepressant use in pregnancy, potentially due to confounding by indication. We assessed the association of antidepressant continuation in pregnancy with GDM, as well as blood glucose levels, after accounting for confounding. Methods: We conducted a retrospective cohort study of singleton live births from 2001 to 2014 to women enrolled in Kaiser Permanente Washington, an integrated health care delivery system, utilizing electronic health data and linked Washington State birth records. We required that women have ≥1 antidepressant prescription fills ≤6 months before pregnancy. Women with an antidepressant fill during pregnancy were categorized as "continuers" (n = 1634); those without a fill were "discontinuers" (n = 1211). We calculated relative risks (RRs) for GDM and mean differences in screening blood glucose levels using generalized estimating equations with inverse probability of treatment weighting to account for baseline characteristics, including mental health conditions and indicators of mental health severity. Results: Compared with discontinuers, antidepressant continuers had comparable risk of GDM (RR: 1.10; 95% confidence interval [CI], 0.84‐1.44) and blood glucose levels (mean difference: 2.3 mg/dL; 95% CI, −1.5 to 6.1 mg/dL). We observed generally similar results for specific antidepressants, with the potential exceptions of risk of GDM associated with sertraline (RR: 1.30; 95% CI, 0.90‐1.88) and venlafaxine (RR: 1.52; 95% CI, 0.87‐2.68), but neither association was statistically significant. Conclusions: Our study suggests that overall, women who continue antidepressants in pregnancy are not at increased risk for GDM or higher blood glucose, although further study may be warranted for sertraline and venlafaxine.